2013
DOI: 10.1002/pssa.201300110
|View full text |Cite
|
Sign up to set email alerts
|

Afterglow and thermoluminescence properties in HPHT diamond crystals under beta irradiation

Abstract: The behaviour of afterglow (AG) and thermoluminescence (TL) in nine beta-irradiated HPHT Ib type diamond crystals is presented. The transparent yellow synthetic crystals (Sumicrystal, UP-3510) were purchased from ProDiamond, Germany. Immediately after irradiation, the crystals exhibit pronounced AG (phosphorescence) caused by thermal emptying of the traps responsible for the low temperature TL peaks. All AG decay curves are well fitted with the sum of one, two or three exponential decays with the same decay li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The main TL properties of the HPHT diamond crystals were reported elsewhere. [10][11][12][13][14][15][16][17][18][19] Nanocrystalline diamond has received increasing attention because of its unique perspectives in biomedical applications. But up to now only few works devoted to study nanodiamond TL properties have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main TL properties of the HPHT diamond crystals were reported elsewhere. [10][11][12][13][14][15][16][17][18][19] Nanocrystalline diamond has received increasing attention because of its unique perspectives in biomedical applications. But up to now only few works devoted to study nanodiamond TL properties have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Another synthetic diamond is high pressure–high temperature (HPHT) diamond that is commercially available since 1950s with main application as cutting and drilling tools. The main TL properties of the HPHT diamond crystals were reported elsewhere …”
Section: Introductionmentioning
confidence: 99%
“…This aspect, entails that such composite materials behave in front of the radiation of a variety of ways to interact with the treated tissue, making it difficult for direct application in radiation therapy, a procedure widely used today for the treatment of cancer, if not the most common, and of special interest in the application of these devices. Recently, the synthetic diamond grown by the technique of high-pressure and high-temperature (HPHT) has been proposed as a detector of ionizing radiation Low, et al, 2011;Meléndrez, et al, 2006;Chernov, et al, 2013;Gil et al, 2014;Gil et al, 2015. The importance of this material lies in its physical and chemical properties, as it has a Zeff=6 (atomic number-cash) equivalent to the human tissue, this is a relevant feature in a dosimeter for radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the defects created by the presence of these impurities could lead to instability of the HPHT diamond as a dosimeter. Treatments that use high‐energy radiation or thermal annealing have proven to facilitate the observation of individual impurity ions, paramagnetic defects, or to enhance the thermoluminescence (TL) efficiency in HPHT diamonds . Previously, it has been reported an improvement of ∼5% in TL reproducibility on HPHT type Ib synthetic diamond exposed to β‐radiation after a 1073 K thermal annealing process and/or high dose γ‐irradiation .…”
Section: Introductionmentioning
confidence: 99%